2011
DOI: 10.1155/2012/696418
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐Catalytic Ozonation of 4‐Nitrochlorobenzene in Aqueous Solutions

Abstract: In this paper, efficiency of nano-ZnO particles on catalytic ozonation of 4-nitrochlorobenzene (4NCB) using semi-batch reactor has been studied at various pHs. During the catalytic ozonation, TOC and concentration of nitrate ions was monitored. Results indicate that degradation of 4NCB was improved by combination of nano-ZnO with ozone. The effect of ZnO particle size and pH are also examined. According to the results, concentration of 4NCB decreased with increasing of particle size from nanosized to microsize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…ZnO NPs catalyzed ozonation was investigated by Tabatabaei et al for the degradation of 4-nitrochlorobenzene (51). They found that a pH of 3 was the optimum pH for greatest removal efficiency.…”
Section: Advances In Ozonation Applications While Employing Nanomatermentioning
confidence: 99%
“…ZnO NPs catalyzed ozonation was investigated by Tabatabaei et al for the degradation of 4-nitrochlorobenzene (51). They found that a pH of 3 was the optimum pH for greatest removal efficiency.…”
Section: Advances In Ozonation Applications While Employing Nanomatermentioning
confidence: 99%